Increasing the Yield of Green Mustard (Brassica juncea L.) by Using a Dose of Goat Manure Tricho POC Fertiliser - Ohorella, Zainuddin; Maruapey, Ajang; Sangadji, Zulkarnaen; Ulima, Nurida (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
One type of vegetable commodity is very popular with the people of Indonesia, namely mustard greens (Brassica juncea L.) because it has a number of minerals, vitamins, carbohydrates and vegetable proteins that are beneficial to the health of the human body. Green mustard production is relatively good and has a relatively short harvest age of 40-50 days, so it is very feasible to be cultivated in a competitive cultivation system because it has good market opportunities so that it can provide adequate benefits in increasing farmers' income. The research was conducted in July-September 2023 using RAK with 5 treatment levels of goat manure Tricho POC organic fertiliser dosage. K0 = without using Tricho POC goat manure fertiliser (control), K1 = Tricho POC goat manure 5 ml/litre water, K2 = Tricho POC goat manure 10 ml/litre water, K3 = Tricho POC goat manure 15 ml/litre water, K4 = Tricho POC goat manure 20 ml/litre water. A dose of 20 ml/litre of tricho POC goat manure water, is the best dose treatment in increasing the growth and yield of green mustard plants.